2022
DOI: 10.3390/cancers14030602
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence Risk for Primary Glaucoma and Its Subtypes following Chronic Exposure to Ionizing Radiation in the Russian Cohort of Mayak Nuclear Workers

Abstract: Secondary glaucoma is a typical normal tissue complication following radiation therapy involving ocular radiation exposure at high fractionated dose (several tens of Gy). In contrast, recent studies in acutely exposed Japanese atomic bomb survivors showed a significantly increased risk for normal-tension glaucoma (NTG, a subtype of primary open-angle glaucoma) at much lower dose, but such information is not available in any other cohorts. We therefore set out to evaluate the incidence of risk for primary glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The increased risk of NTG by irradiation has been reported 6 , 56 , although its mechanism remains unclear. In the hippocampus of adult brains, radiosensitive neural precursor cells exist, and radiation exposure can trigger the development of dementia several years later 3 , 11 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of NTG by irradiation has been reported 6 , 56 , although its mechanism remains unclear. In the hippocampus of adult brains, radiosensitive neural precursor cells exist, and radiation exposure can trigger the development of dementia several years later 3 , 11 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects of radiation exposure on the eye, evidence has accumulated for cataracts following moderate or high doses [37][38][39] (along with limited evidence at low doses [40,41]) and neovascular glaucoma following high doses [9]. Azizova et al [19] reported a significantly increased radiation risk of normal-tension glaucoma (a subtype of primary open-angle glaucoma) in a cohort of Russian Mayak nuclear workers, confirming observations in Japanese atomic bomb survivors [42][43][44]. Thariat et al [20] reviewed the current knowledge on normal tissue complications in the eye and orbit (e.g., the lacrimal gland, eyelashes, eyelids, cornea, lens, macula/retina, optic nerves and chiasma) following radiotherapy.…”
Section: Sensory Systemmentioning
confidence: 99%
“…Therefore, this Special Issue ( ) aims to serve as a forum to gather the latest developments and discuss future prospects in the field of normal tissue responses to radiation exposure. The Special Issue consists of 18 articles [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] outlining the cancer and non-cancer effects of radiation occurring in various tissues (e.g., those in the circulatory, sensory, nervous, respiratory, and reproductive systems), including studies on mitigation strategies and biomarkers, as outlined below.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mayak cohort, incidence of primary glaucoma (i.e., POAG plus PACG) and POAG in workers followed up until 2008 was not associated with radiation exposure, with ERR/Gy (brain dose) of 0.01 (95% CI: –0.13, 0.19) and 0.0003 (95% CI: –0.13, 0.19), respectively ( 111 ). In Mayak workers followed up until 2018, NTG incidence showed an increased risk at ≥1 Gy with ERR/Gy of 0.53 (95% CI: 0.01, 1.68), whereas incidence of HTG, POAG (i.e., HTG plus NTG) and PACG was not associated with radiation exposure ( 112 ). The USRT cohort showed a suggestive but nonsignificant decrease with dose for self-reported glaucoma in aggregate, with ERR/Gy of –0.57 (95% CI: –1.46, 0.40) ( 113 ).…”
Section: Recent Developments For Effects On the Eyementioning
confidence: 99%